Enhancing building energy performance by effectively using phase change material and dynamic insulation in walls. (1st February 2021) - Kishore, Ravi Anant; Bianchi, Marcus V.A.; Booten, Chuck; Vidal, Judith; Jackson, Roderick
Highlights: Dynamic insulation material and system (DIMS) and Phase change material (PCM) for buildings. DIMS-PCM-integrated walls under various climatic conditions are examined. PCM-DIMS-integrated wall performs better than DIMS-integrated or PCM-integrated walls. Up to 15–72% reduction in annual heat gain and 7–38% reduction in annual heat loss. Abstract: Deploying phase change materials (PCMs) in building envelopes can be effective in reducing space heating/cooling loads and providing load shedding and shifting capacity. However, the full potential of PCM-integrated envelopes can only be harnessed if the PCM undergoes phase change using free ambient heating/cooling, and the stored energy is effectively transferred between the exterior and the interior environments. Traditional thermal insulation (with a fixed thermal resistance) limits PCM utilization, which restrains the energy saving potential of a PCM-integrated envelope to a small percentage. Proposed dynamic insulation material and system (DIMS) provides the option of varying its thermal resistance based on the indoor and outdoor conditions. Although it has been established that employing PCM as well as DIMS in building envelopes separately improves buildings' energy performance, no prior studies that analyzed the combined influence of both technologies were identified. In this study, we examine a novel wall design, comprising a layer of PCM between two layers of DIMS. We note that the PCM-DIMS-integrated wall provides significantly higher energy saving potential than the DIMS-only integrated wall or the PCM-only integrated wall in all the climates and wall orientations analyzed in this study. Depending on the climate, the PCM-DIMS-integrated wall could provide 15–72% reduction in annual heat gain and 7–38% reduction in annual heat loss. The analysis presented in this study supports the need to develop scalable dynamic insulations combined with thermal energy storage systems for buildings.